Individual differences in brain aging: heterogeneity in cortico-hippocampal but not caudate atrophy rates. (5th October 2022) - Nyberg, Lars; Andersson, Micael; Lundquist, Anders; Baaré, William F C; Bartrés-Faz, David; Bertram, Lars; Boraxbekk, Carl-Johan; Brandmaier, Andreas M; Demnitz, Naiara; Drevon, Christian A; Duezel, Sandra; Ebmeier, Klaus P; et al.
Abstract: It is well documented that some brain regions, such as association cortices, caudate, and hippocampus, are particularly prone to age-related atrophy, but it has been hypothesized that there are individual differences in atrophy profiles. Here, we document heterogeneity in regional-atrophy patterns using latent-profile analysis of 1, 482 longitudinal magnetic resonance imaging observations. The results supported a 2-group solution reflecting differences in atrophy rates in cortical regions and hippocampus along with comparable caudate atrophy. The higher-atrophy group had the most marked atrophy in hippocampus and also lower episodic memory, and their normal caudate atrophy rate was accompanied by larger baseline volumes. Our findings support and refine models of heterogeneity in brain aging and suggest distinct mechanisms of atrophy in striatal versus hippocampal-cortical systems.